2022
DOI: 10.3758/s13414-022-02484-5
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nociceptive detection thresholds and cortical evoked potentials: Go/no-go versus two-interval forced choice

Abstract: Pain scientists and clinicians search for objective measures of altered nociceptive processing to study and stratify chronic pain patients. Nociceptive processing can be studied by observing a combination of nociceptive detection thresholds and evoked potentials. However, it is unknown whether the nociceptive detection threshold measured using a go-/no-go (GN) procedure can be biased by a response criterion. In this study, we compared nociceptive detection thresholds, psychometric slopes, and central evoked po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Other studies in patient groups with the same method have been able to make similar observations, yet with a lower slope in response to both the single-and double pulse stimuli [17,18]. While more research is required to understand these differences, factors which are known to contribute differentially to the SP slope as compared to the DP slope, are the peripheral-and central sensitivity of the nociceptive function [10], as well as the internal criterion [26]. As such, it is recommended that future research not only evaluates what factors affect the outcome of NDT measurements, but also whether identified factors might affect NDTs of different stimulus types differently.…”
Section: B Exploration Of Ndt Differences Between Ra and Hcmentioning
confidence: 65%
See 1 more Smart Citation
“…Other studies in patient groups with the same method have been able to make similar observations, yet with a lower slope in response to both the single-and double pulse stimuli [17,18]. While more research is required to understand these differences, factors which are known to contribute differentially to the SP slope as compared to the DP slope, are the peripheral-and central sensitivity of the nociceptive function [10], as well as the internal criterion [26]. As such, it is recommended that future research not only evaluates what factors affect the outcome of NDT measurements, but also whether identified factors might affect NDTs of different stimulus types differently.…”
Section: B Exploration Of Ndt Differences Between Ra and Hcmentioning
confidence: 65%
“…suggest that NDT outcomes are also sensitive to changes in central nociceptive functioning. Recently, it was found that the NDT can be affected by criterium formation, with some stimulus types being more sensitive than others[26]. Lastly, it is thought -but not yet evaluated -that NDTs are affected by factors such as the level of attention and internal noise.…”
mentioning
confidence: 99%